Chemical constituents from stem barks and roots of murraya koenigii (Rutaceae) - Abu Bakar, Noor Haslizawati; Sukari, Mohd Aspollah; Rahmani, Mawardi; Md. Sharif, Atan; Khalid, Kaida; Yusuf, Umi Kalsom (Universiti Kebangsaan Malaysia, 2007)
Four carbazole alkaloids, identified as mahanimbine (1), girinimbine (2), murrayanine (3) murrayafoline-A (4) and one triterpene were isolated from stem bark and roots of Murraya koenigii. The structures of these compounds were established by infra-red (IR), mass spectrometry (MS) and nuclear magnetic resonance (1H NMR, 13C NMR, HMQC and HMBC) spectroscopy.